Language Minority Education – priority target group? - Blažević Simić, Ana (Array, 2014)
In the Croatian education system, national minorities are declaratively recognized as a priority target group and have been offered some specific educational programs which guarantee them the right to education in the language and script of national minorities. Yet the author considers this minority education policy and analyses its realization level based on several domestic and international recent research, legal framework and related international reports and recommendations, and consequently suggests possible solutions for the realization of a more efficient educational process both in the language and script of national minorities as in education in general.